Profil Pemahaman Konsep dan Miskonsepsi Peserta Didik pada Materi Gelombang Bunyi melalui LKPD Berbasis Simulasi PhET Sound Waves - Afrizal; Lina Aviyanti; Ratih Sirnawati; Alfiansah Sandion Prakoso (Jurnal Pendidikan dan Ilmu Fisika, 2026)
This study aimed to profile students' conceptual understanding and identify misconceptions on sound waves through PhET Sound Waves simulation-based worksheets (LKPD). A quantitative descriptive method was employed involving 36 eleventh-grade students divided into nine groups. Data were collected from students' worksheet responses and analyzed using four conceptual understanding indicators adapted from Anderson and Krathwohl: explaining, interpreting, applying, and connecting. The results showed that the applying indicator achieved the highest performance (100%), followed by interpreting (88.9%), connecting (66.7%), and explaining (44.4%). The findings revealed that students demonstrated strong procedural and interpretative abilities but experienced difficulties in explaining underlying physical concepts. The most common misconception was the belief that the speed of sound depends on frequency. This misconception was associated with inaccuracies in measuring wavelength using the virtual simulation, which led students to misinterpret fluctuations in calculated sound speed. These findings indicate that PhET-based worksheets effectively support conceptual interpretation and mathematical application; however, teacher guidance during reflection remains necessary to prevent misconceptions and strengthen conceptual understanding.